The Impact of Sexual Abuse, Family Violence/Conflict, Spirituality, and Religion on Anger and Depressed Mood Among Adolescents - Sigurvinsdottir, Rannveig; Asgeirsdottir, Bryndis Bjork; Ullman, Sarah E.; Inga Dóra Sigfúsdóttir 1967- (2021)
Stressful life experiences, such as sexual abuse and family violence/conflict, relate to an increased risk of mental health problems. Religion and spirituality may prevent this negative impact, but religion and spirituality are lower among survivors of stressful life experiences. To explore this effect, we examined the relationship between childhood sexual abuse and family violence/conflict on anger and depressed mood. Survey data were collected from a large population–based sample of Icelandic adolescents (N = 7,365) on their stressful life experiences, religion, spirituality, and mental health. Survivors of stressful life experiences (sexual abuse or family violence/conflict) were significantly lower on religion and spirituality than others. A hierarchical linear regression showed that stressful life experiences contributed uniquely to higher levels of anger and depressed mood. Spirituality was associated with decreased anger and depressed mood. The religion of parents and peers was also associated with decreased anger. Religious participation, on the contrary, did not have a relationship with mental health outcomes. In addition, the negative association between spirituality and anger was stronger among survivors of sexual abuse than nonabused individuals. These results confirm previous research, indicating that survivors of stressful life experiences may experience less religion and spirituality. The results also extend existing knowledge by showing that spirituality may be even more beneficial among sexual abuse survivors, as a protective factor against anger. These findings can help in the minimization of the negative mental health impact of stressful life experiences.
Keywords: Spirituality; Religion; depressed mood; Anger; family violence/conflict; Sexual Abuse